Measurement of the essential function in public health N.º 11: Reduction of the impact of emergencies and disasters in health in health directorates, 2019 - Bazán Vargas, Kieffer Segundo (2023)
Objective: To measure the performance profile of the essential function in public health (EPHF) N.° 11: reduction of emergencies and disasters in health. Method: It is a basic and descriptive research, with a population and sample of 25 health departments in the country. The instrument used was a questionnaire adapted and defined by PAHO-WHO. Results: The performance profile was rated as "lower average performance" with a value of 0.41. The strengths identified were the following: coordination and alliances with other institutions, and advice and technical support at the subregional levels. and The weaknesses were the following: management and development of standards and guidelines. The main areas to be strengthened are the following: response planning, assisted patient transport system, development and implementation of preparedness standards. The evaluation of the measurement between the years 2006 and 2019, at a global level, shows that the performance profile of the EPHF N.º 11 for the year 2006 had a percentage of 0.56, placing it in the "upper medium" performance quartile and for 2019 a "medium upper" performance profile. lower” with a 0.41. There is evidence of a decrease in the percentage of the performance profile by 0.15 %. According to the ranking, the first place in performance is the Apurímac Health Directorate with 0.80. Conclusions: The FESP presents a decrease in its performance profile, which would lead the sector to strengthen its indicators.